ZAKAT EMPOWERMENT MODEL TROUGH ISLAMIC CORPORATE SOCIAL RESPONSIBILITY OF BANK SYARIAH INDONESIA - Rusanti, Ega; Herianingrum, Sri; Syarifuddin, Syarifuddin; Sofyan, Andi Syathir (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the potential and collaborative scheme between BSI and IMIs in utilizing ICSR zakat more productively. The research method used is qualitative research with a grounded approach which begins with analyzing empirical data and literature leading to the conceptual-theoretical level. The author conducted content analysis on secondary data in the form of BSI 2021 journals and sustainability reports. The results of the research show that there is potential for collaboration between BSI and IMIs in terms of utilizing zakat to improve the living standards of the poor and encourage micro-enterprises through the qadhrul hasan financing scheme where the beneficiary will only be charged return on initial capital then profits can be given to the manager. This collaboration will not only provide social benefits to both parties but will also increase the commercial function where people will feel the direct impact of the benefits of Islamic financing so that they can be more educated and will ultimately increase Islamic financial inclusion in Indonesia.